Conversations with Dr. Rowena Spencer: America's First Woman Pediatric Surgeon - Fishkin, Charles (Ars Medica, 2024)
Rowena Spencer (1922-2014) was one of the first women in the country—if not the first—to specialize in pediatric surgery. She was born in Shreveport Louisiana and was the daughter of an orthopedic surgeon. She received her medical degree from Johns Hopkins (1947). She continued her training as an intern is surgery at Johns Hopkins (1947-48); a surgical resident at the Children’s Hospital of Philadelphia (1948-49); and an assistant in surgery at Tulane University (1949-50). She then held residencies in pediatrics and surgery at Louisiana State University (1950-53. She pursued additional specialized training in pediatric surgery at the Karolinska Institute in Stockholm (1954). She joined the faculty at Louisiana State University while completing her surgical residency (1952). She remained at LSU until 1968. She retired from surgery in 1984. During her last several years, she shared her thoughts about her career and the early years of pediatric surgery. Her conversations provide examples of her distinctive way of speaking—both formal and precise yet she also self-deprecatory and spontaneous.